The Role of Dozer Volunteers in the Electoral Winning Strategy of Andi Asman Sulaiman and Andi Akmal Pasluddin in the Political Contestation of Bone Regency - Hidayat, Andi Rahmat Nizar; Cahyo Nugroho, Tri (Indonesian Journal of Political Studies, 2026)
This research analyzes the role of "Dozer Volunteers" in the victory of the BerAMAL pair in the 2024 Bone Regency Election (199,954 votes; winning in 24 districts). Adopting a qualitative case study approach, the analysis integrates Political Mobilization Theory, Brokerage Politics, and Electoral Geography. The findings indicate a positive correlation between volunteer density and vote acquisition; dominant victories were observed in Libureng and Kahu (high volunteer density) compared to Tonra (lower density). Village Coordinators (Kordes) played a vital role as political brokers, bridging candidates and voters through local social networks. In conclusion, BerAMAL's victory was not only supported by formal party machinery but was significantly determined by structured, adaptive, and village-based non-party volunteer mobilization. This study provides empirical evidence of the strategic role of volunteer networks in strengthening the effectiveness of grassroots mobilization in local political contests